Usability and Safety in Electronic Medical Records Interface Design: A Review of Recent Literature and Guideline Formulation. (August 2015) - Zahabi, Maryam; Kaber, David B.; Swangnetr, Manida
Objective: The objectives of this study were to (a) review electronic medical record (EMR) and related electronic health record (EHR) interface usability issues, (b) review how EMRs have been evaluated with safety analysis techniques along with any hazard recognition, and (c) formulate design guidelines and a concept for enhanced EMR interfaces with a focus on diagnosis and documentation processes. Background: A major impact of information technology in health care has been the introduction of EMRs. Although numerous studies indicate use of EMRs to increase health care quality, there remain concerns with usability issues and safety. Method: A literature search was conducted using Compendex, PubMed, CINAHL, and Web of Science databases to find EMR research published since 2000. Inclusion criteria included relevant English-language papers with subsets of keywords and any studies (manually) identified with a focus on EMR usability. Results: Fifty studies met the inclusion criteria. Results revealed EMR and EHR usability problems to include violations of natural dialog, control consistency, effective use of language, effective information presentation, and customization principles as well as a lack of error prevention, minimization of cognitive load, and feedback. Studies focusing on EMR system safety made no objective assessments and applied only inductive reasoning methods for hazard recognition. Conclusion: On the basis of the identified usability problems and structure of safety analysis techniques, we provide EMR design guidelines and a design concept focused on the diagnosis process and documentation. Application: The design guidelines and new interface concept can be used for prototyping and testing enhanced EMRs.